Winning at new products : creating value through innovation - Cooper, Robert G. 1943- (Basic Books, 2011)
"For more than two decades, Winning at New Products has served as the bible for product developers everywhere. In this fully updated and expanded edition, Robert Cooper demonstrates why consistent product development is so vital to corporate growth and how to maximize your chances of success."--Zadní s. obálky
Keywords: management inovací; výrobky; innovation management; commercial products; příručky; handbooks, manuals, etc